A CASE STUDY ON NEW VEHICLE INVESTMENT FOR THE TOURIST TRANSPORTATION RENTAL BASED ON BWM AND SAW - SAPUTRA, BAGAS AJI; Kurniawan, V. Reza Bayu; Yunitasari, Elly Wuryaningtyas (Universitas Muria Kudus, 2025)
Article history : The rapid growth of the tourism industry, especially in Indonesia, has positively impacted various other sectors. This growth has indirectly spurred the development of supporting businesses, predominantly small and medium-sized enterprises (SMEs), such as tourist transportation rentals. Rising tourist demands for transportation necessitate that entrepreneurs in this industry adapt quickly, including investing in the latest vehicle units. However, investing in new vehicles is challenging, especially for small-scale rental owners. They must carefully calculate their investment, considering various potential risks. Therefore, this study recommends alternatives for new vehicle investments in tourist transportation rentals based on BWM and SAW. A case study on small-scale rental businesses in Yogyakarta has been selected. The results indicate that five criteria must be considered for new vehicle investments in tourist rentals: vehicle type (C1), fuel consumption (C2), engine specifications (C3), rental price (C4), product lifetime (C5), and price (C6). The optimal weights of these criteria are determined using BWM to rank five investment alternatives: KIZ, HIC, AVZ, BRI, and SGR. The findings suggest KIZ as the potential top investment priority, followed by AVZ, BRI, SGR, and HIC.